In vivo Raman spectroscopy for bladder cancer detection using a superficial Raman probe compared to a nonsuperficial Raman probe. Issue 6 (16th March 2022) - Stomp‐Agenant, Michelle; van Dijk, Thomas; R. Onur, Alexander; Grimbergen, Matthijs; van Melick, Harm; Jonges, Trudy; Bosch, Ruud; van Swol, Christiaan
Abstract: Raman spectroscopy is promising as a noninvasive tool for cancer diagnosis. A superficial Raman probe might improve the classification of bladder cancer, because information is gained solely from the diseased tissue and irrelevant information from deeper layers is omitted. We compared Raman measurements of a superficial to a nonsuperficial probe, in bladder cancer diagnosis. Two‐hundred sixteen Raman measurements and biopsies were taken in vivo from at least one suspicious and one unsuspicious bladder location in 104 patients. A Raman classification model was constructed based on histopathology, using a principal‐component fed linear‐discriminant‐analysis and leave‐one‐person‐out cross‐validation. The diagnostic ability measured in area under the receiver operating characteristics curve was 0.95 and 0.80, the sensitivity was 90% and 85% and the specificity was 87% and 88% for the superficial and the nonsuperficial probe, respectively. We found inflammation to be a confounder and additionally we found a gradual transition from benign to low‐grade to high‐grade urothelial carcinoma. Raman spectroscopy provides additional information to histopathology and the diagnostic value using a superficial probe. Abstract : In vivo, we compared a superficial to a nonsuperficial Raman probe, in 104 bladder cancer patients. The area under the receiver operating characteristic curve improved from 0.80 to 0.95 and sensitivity from 85% to 90% when using the superficial probe. The specificity was approximately equal: 87% vs 88%. Thus, the superficial probe improves Raman bladder cancer diagnosis. Inflammation was a confounder. An indication of gradual transition from benign to low‐grade to high‐grade urothelial carcinoma was found.